The Impact of Evidence on the Difference of Critics in Tarjeeh between Narratives and Their Ilal | أثر القرائن في اختلاف النقاد في الترجيح بين الروايات وإعلالها - Abdelrhman Mohammad Mashagba (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
This study deals with one of the most significant issues of hadith science, which is the issue of the evidence and their impact on the difference between the judgement of the critics on hadiths and outweighing (Tarjeeh) them. It also aimed to show its role in obtaining a decision regarding the different hadiths in terms of their correction or explanation among the critics. To achieve this objective, I used the incomplete inductive approach to collect the models that I reviewed and studied. Then I applied the deductive and critical approach in analyzing and studying this data.  I used the previous methods to obtain accurate results concerning each issue of this research and to indicate the extent of its relevance and strength according to the hadith criticism. This research is divided into different topics including an introduction, and four main topics than a conclusion that explains the results of this research. The most important of which are: One of the features of the critical approach among the modern scholars in the science of Ilal Al- hadith is the search for evidence in each hadith to outweigh one hadith over the other. Also deeming the judgments of the critics on the narrations without considering the evidence that they considered when judging al-hadith and leads to the occurrence of the error in the outweighing between the narrations.